Using Glycated Albumin and Stimulated C-Peptide to Define Partial Remission in Type 1 Diabetes - Shi, Mei; Ji, Xiaolin; Xie, Yuting; Zhong, Ting; Tang, Rong; Fan, Li; Li, Xia (Frontiers in Endocrinology, 2022)
Objective To propose a new definition of partial remission (PR) for patients with type 1 diabetes (T1D) of all-ages using insulin dose and glycated albumin (GA), and find the optimal cut-off values for stimulated C-peptide to diagnose PR in different age-groups. Research Design and Methods Patients with newly diagnosed T1D (n=301) were included. GA/insulin dose was used to diagnose PR, and insulin dose-adjusted glycated albumin (IDAGA) was proposed to facilitate clinical application. The optimal diagnostic levels of IDAGA and stimulated C-peptide were determined in different age-groups (≤ 12y, 12-18y and ≥ 18y). Furthermore, the diagnostic consistency between different PR definitions was studied. Results GA≤ 23%/insulin dose ≤ 0.5u/kg/day was used to define PR, and IDAGA (GA (%) + 40 * insulin dose(u/kg/day)) ≤ 40 was feasible in all age-groups. Whereas, the optimal diagnostic level showed difference for stimulated C-peptide (265.5, 449.3 and 241.1 pmol/L for the ≤ 12y, 12-18y and ≥ 18y age-group, respectively). About 40% of patients met the PR definition by stimulated C-peptide but not GA/insulin dose or IDAGA, who showed dyslipidemia and higher insulin resistance. Conclusions A new definition of the PR phase is proposed using GA/insulin dose, and the calculated IDAGA≤ 40 applies to all age-groups. The stimulated C-peptide to diagnose PR is the highest in the 12-18y age-group, which reflects the effect of puberty on metabolism. For patients with insulin resistance, it is not recommended to use stimulated C-peptide alone to diagnose PR.